1999
DOI: 10.2166/wst.1999.0527
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rainfall intensity on soil erosion and particulate phosphorus transfer from arable soils

Abstract: Soil erosion, in the form of transported suspended sediment in overland flow, is often associated with high rates of particulate phosphorus (PP) (total P>0.45 μm) transfer from land to watercourses. Particulate P may provide a long-term source of P for aquatic biota. Twenty-two sites for winter overland flow monitoring were selected in south-west England within fields ranging from 0.2–3.8 ha on conventionally-managed arable land. Fields were situated on highly porous, light textured soils, lacking imper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 0 publications
3
44
0
1
Order By: Relevance
“…Sandy soils are particularly vulnerable to erosion due to low SOM content and poor structural stability, which predisposes the soil to disaggregation under raindrop impact and a subsequent development of a surface crust, reduction of infiltration rate and surface runoff (Quinton and Catt 2004). Long-term arable use and modern cultivation methods can result in light textured soils capping (a surface crust caused by heavy raindrops on finely cultivated soils) under rain impact (Fraser et al 1999). In a review of critical levels of SOC in tillage land in Ireland, Spink et al (2010) concluded that soil function is unlikely to be adversely affected when SOC is above a threshold of 2% (equivalent to 3.4% SOM).…”
Section: Soil Typementioning
confidence: 99%
See 1 more Smart Citation
“…Sandy soils are particularly vulnerable to erosion due to low SOM content and poor structural stability, which predisposes the soil to disaggregation under raindrop impact and a subsequent development of a surface crust, reduction of infiltration rate and surface runoff (Quinton and Catt 2004). Long-term arable use and modern cultivation methods can result in light textured soils capping (a surface crust caused by heavy raindrops on finely cultivated soils) under rain impact (Fraser et al 1999). In a review of critical levels of SOC in tillage land in Ireland, Spink et al (2010) concluded that soil function is unlikely to be adversely affected when SOC is above a threshold of 2% (equivalent to 3.4% SOM).…”
Section: Soil Typementioning
confidence: 99%
“…It has been shown that approximately 90-95% of soil erosion occurs during the most severe 2% of storms (Winegardner 1996). Erosion also occurs over periods of prolonged lower-intensity rainfall (Fraser et al 1999;Robinson 1999). Mean annual precipitation for Ireland ranges from 750-1000mm on the eastern half of the country to 1000-1400mm on the western half (Met Éireann 2012).…”
Section: Precipitation (Amount Duration and Intensity)mentioning
confidence: 99%
“…Torrential rain is widely believed to considerably contribute to sediment erosion (Summer 1989;Acornley and Sear 1999;Fraser et al 1999;Descroix and Gautier 2002). Additionally, both droughts followed by heavy rain events and long consecutive rain events on already saturated soil can trigger erosion; the latter at an even higher extent than single day heavy rainfall events (Prasuhn 2003).…”
Section: Effects Of Changes In Precipitation Patternsmentioning
confidence: 99%
“…Soil erosion per se has been described many times (Quinton, 1997) and in the context of P transfer is important for particulate loss (Catt et al, 1994;Fraser et al, 1998). Some studies showed that soil solution and river water contain a continuum of sub-0.45 Am sized particles, often smaller than 10,000 Da molecular weight (Haygarth et al, 1997;Heathwaite et al, in press).…”
Section: Mobilisationmentioning
confidence: 99%